PELATIHAN PUKULAN BAYANGAN LEBIH BAIK DARI PADA PUKULAN BIASA DALAM MENINGKATKAN VO2MAX DAN DAYA TAHAN OTOT LENGAN PADA ATLET TINJU AMATIR KABUPATEN LOMBOK TENGAH (NTB) - Anam, Khaerul; Adiatmika, I P G; Griadhi, I Putu Adiartha; Muliarta, I Made; Sundari, Luh Putu Ratna; Purnawati, Susy (Sport and Fitness Journal; Volume 7, No.3, September 2019DO - 10.24843/spj.2019.v07.i03.p04, 2019)
Boxing is the basic gesture for all martial arts, because all of them definitely use the shadow shot and common shot. These two types of shots are related each other because anaerobic capacity must go along with aerobic capacity.To attain the proper knowledge about the method of shadow shot and common shot in increasing VO2max for the endurance of arm muscles for boxer athletes in Central Lombok Regency. Research was experimental with pre-test and post-test control group design, this research wasconducted in Pertina Lombok Tengah Regency. The research subjects involved 15 people divided into two groups, 7 and 8 samples respectively. The control group given only shadow shot while treatment group given common shot. This training held 3 times a week in six weeks for both groups. The analyses data with independent t-test. Researcher found The endurance of arm muscles (p<0,05) that training in twu group his’not significant to VO2max (p>0,05). Keywords: Shadow blows, regular blows, Boxing, VO2max and Endurance of arm Muscl